MOTIVATION, ATTITUDE, NEED, AND EVALUATION OF THE STUDENTS OF IAIN MATARAM IN LEARNING ENGLISH AS A GENERAL SUBJECT TO DEAL WITH GLOBALIZATION ERA - Ribahan Ribahan (Lingua Scientia, 2017)
This study aims at investigating motivation, attitude, needs, and evaluation of the students of IAIN Mataram in learning English as a general subject. The data were gathered from questionnaire and they were presented descriptively. The result of questionnaire showed that the students considered English very important (98%). The motivation of the students in learning English was very high (93%) and they learned English for intrinsic reasons (77%). The attitude of the students in learning English was very positive (84%). The students preferred learning English visually to learning orally (81%). The teacher taught seriously (95%), the teacher gave various tasks ((91%), and the teacher gave motivation to the students (95%). The class size supported the teaching and learning process (99%). The students competed seriously in learning English (77%). The students needed English relevant to their content subject (90%) and they needed more reading skill than the three other skills (83%).